(untitled) (Philological Studies, 2019)
The paper investigates the meaning of “Perm period” in the artistic progress and in the way of life of the Russian émigré poet of Polish origin Nadezhda Birskaya, who moved to the USA in 1924. The paper proves, that years of attending the University of Perm were formative for her ideological position. Her identity contaminated traces of Russian and Polish culture practices, as well as her deep experience of poetic self-representation and public activity in the years of Russian Revolution.